Development and Evaluation of Positive Adolescent Training through Holistic Social Programs (P.A.T.H.S.) - SHEK, Daniel T.L.; Sun, Rachel C. F.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2013)
This book outlines the development, implementation and evaluation of a project entitled "P.A.T.H.S. to Adulthood: A Jockey Club Youth Enhancement Scheme," with P.A.T.H.S. denoting Positive Adolescent Training through Holistic Social programmes. This pioneer project was conducted in Hong Kong between 2005 and 2012 with more than 210,000 participants. Its goal was to help students meet various challenges in their path to adulthood, with a focus on their psychosocial competencies, developmental assets and the promotion of healthy peer relationships. The project was initiated by The Hong Kong Jockey Club Charities Trust in collaboration with the Government$1 (Bs Social Welfare Department, Education Bureau and five universities in Hong Kong. Edited by the researchers of the project, Development and Evaluation of Positive Adolescent Training through Holistic Social Programs explores the nature of positive youth development (PYD), the application of PYD constructs to youth programs and implementation issues. Using multiple strategies, the book evaluates the overall effectiveness of the P.A.T.H.S. school-based program and reveals that stakeholders had positive perceptions of the project, its implementers and benefits. Students in the program showed better positive development and displayed lower levels of substance abuse and delinquent behavior than students in the control schools. The book also details lessons learned, emergent issues, future directions as well as insights into the development of positive youth development programs particularly in Chinese communities. Development and Evaluation of Positive Adolescent Training through Holistic Social Programs will appeal to all educators, administrators, psychologists, social workers and allied profeesionals looking to promote whole-person development in their students, especially those with in interest in education in China.s
Preface -- 1 Adolescent developmental issues in Hong Kong: Phenomena and implications for youth service -- 2 Conceptual framework underlying the development of a positive youth development program in Hong Kong -- 3 Development of a positive youth development program in Hong Kong -- 4 Evaluation of the Project P.A.T.H.S. using multiple evaluation strategies -- 5 Objective outcome evaluation of the Project P.A.T.H.S.: Longitudinal study based on indicators of positive youth development -- 6.Impact of the Project P.A.T.H.S. on adolescent risk behavior: A five-year longitudinal study -- 7 Subjective outcome evaluation based on the program participants: Does dosage matter? -- 8 Subjective outcome evaluation based on the perceptions of the program implementers -- 9 Subjective Outcome Evaluation of the Project P.A.T.H.S.:Secondary analyses of the qualitative data collected from program implementers -- 10 Interim evaluation of Project P.A.T.H.S.:An integration of findings based on program implementers -- 11 Qualitative evaluation of the Project P.A.T.H.S.:Narrative findings based on focus groups with participating students -- 12 Qualitative findings derived from focus groupsbased on the program implementers -- 13 Evaluation based on weekly diaries written by the students -- 14 Evaluation based on personal construct psychology:Findings based on the repertory grid test -- 15 Process evaluation of the Project P.A.T.H.S. in Hong Kong -- 16 Using different programs to help adolescents withgreater psychosocial needs -- 17 Lessons learned, emergent issues, and future directions -- 18 Development of a positive youth development subject in a university context -- 19 Impact of the Project P.A.T.H.S. in China -- 20 Evidence-based positive youth development programs: Insights from the Project P.A.T.H.S.
Keywords: Philosophy (General).; Developmental psychology; Psychological tests and testing; Consciousness; Psychology; Positive Psychology; Child and School Psychology; Personality and Social Psychology; Cognitive Psychology; Psychological Methods/Evaluation.